Metabolic Syndrome is a Risk Factor for Post-Operative Adhesions: Need for Novel Treatment Strategies - Pilpel, Yair; Pines, Guy; Birkenfeld, Andreas; Bornstein, Stefan R.; Miller, Rafael (Hormone and Metabolic Research, 2019)
Metabolic syndrome is a group of disorders which include obesity, diabetes, dyslipidemias, and hypertension. This condition is rapidly increasing in an aging population. The rates of surgery in older patients is also growing and a wide range of operations including minimally invasive procedures is now available for this segment of the population. The number of patients suffering from postoperative adhesions is therefore correspondingly increasing. In addition to preventing and treating the metabolic disease itself, improved therapeutic strategies for the prevention of surgical adhesions have to be developed. Here we review the existing and novel treatment options.
Keywords: diabetes; surgery; adhesions; metabolic syndrome